Numerical Study on the Effect of Horizontally Installed Corrugated Plate Boundary Condition under Blast Load - Riyanto, Raditya D.; , Handayanu; Prastianto, Rudi W. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Blast hazard load on offshore and marine operation resulting very catastrophic failure. Installation of protection devices needs to be applied. There are active and passive protection available. This paper investigates the use of corrugated plate as a passive protection to resist blast loads based on ASCE (American Society of Civil Engineers) - Design of Blast Resistant Building in Petrochemical Facilities. This paper aims to investigate the response in terms of stress, deformation and energy dissipation of corrugated plate with accounting the effect of boundary condition.The horizontally installed corrugated plate is modeled using well known FEA Software, ANSYS. Numerical simulation is validated using meshing sensitivity study. The plate is then loaded by light, medium, and heavy explosions, represented by uniform pressure. Numerical simulation of non-linear structural analysis is performed. Based on the analysis result, it is concluded that the pinned and fixed boundary condition corrugated plate successfully resists the all the blast load variations, but the pinned support gives average better responses.